Estimating the risks of prehospital transfusion of D‐positive whole blood to trauma patients who are bleeding in England. Issue 5 (12th January 2022) - Cardigan, Rebecca; Latham, Tom; Weaver, Anne; Yazer, Mark; Green, Laura
Abstract: Background and Objectives: D‐negative red cells are transfused to D‐negative females of childbearing potential (CBP) to prevent haemolytic disease of the foetus and newborn (HDFN). Transfusion of low‐titre group O whole blood (LTOWB) prehospital is gaining interest, to potentially improve clinical outcomes and for logistical benefits compared to standard of care. Enhanced donor selection requirements and reduced shelf‐life of LTOWB compared to red cells makes the provision of this product challenging. Materials and Methods: A universal policy change to the use of D‐positive LTOWB across England was modelled in terms of risk of three specific harms occurring: risk of haemolytic transfusion reaction now or in the future, and the risk of HDFN in future pregnancies for all recipients or D‐negative females of CBP. Results: The risk of any of the three harms occurring for all recipients was 1:14 × 10 3 transfusions (credibility interval [CI] 56 × 10 2 –42 × 10 3 ) while for females of CBP it was 1:520 transfusions (CI 250–1700). The latter was dominated by HDFN risk, which would be expected to occur once every 5.7 years (CI 2.6–22.5). We estimated that a survival benefit of ≥1% using LTOWB would result in more life‐years gained than lost if D‐positive units were transfused exclusively. These risks would be lower, if D‐positive blood were only transfused when D‐negative units are unavailable. Conclusion: These data suggest that the risk of transfusing RhD‐positive blood is low in the prehospital setting and must be balanced against its potential benefits.